Effect of vaccination and the immunomodulators bacillus of Calmette-Guerin, Avridine and Propionibacterium acnes on rabies in mice - Megid, Jane [UNESP]; Peracolli, MTS; Curi, P. R.; Zanetti, C. R.; Cabrera, W. H.; Vassao, R.; Ito, F. H. (Elsevier B.V., 1998)
Responses: of vaccination and treatment to immunomodulators against rabies in mice were evaluated through macrophage inhibition factor (MIF), intra-pad inoculation (IPI) and serum neutralization (SN) tests and by the detection of gamma-interferon (IFN-gamma). Onco-BCG, Avridine and Propionibacterium acnes were administered to groups of mice. Higher survival rates were found in animals treated with P. acnes. Lower levels of IFN-gamma were observed in the groups of infected and vaccinated mice. The IPI was not effective on detecting the response of delayed-type hypersensitivity. Vaccine induced in the infected animals a more intense response to MIF reaction. (C) 1998 Elsevier B.V. Ltd. All rights reserved.
Keywords: rabies; immunomodulators; cellular immunity; humoral immunity; MIF; -INTERFERON; mice